A sustainable strategy for the straightforward preparation of 2H-azirines and highly functionalized NH-aziridines from vinyl azides using a single solvent flow-batch approach - Andresini, Michael; Degannaro, Leonardo; Luisi, Renzo (Beilstein Journal of Organic Chemistry, 2021)
The reported flow-batch approach enables the easy preparation of 2H-azirines and their stereoselective transformation into highly functionalized NH-aziridines, starting from vinyl azides and organolithium compounds. The protocol has been developed using cyclopentyl methyl ether (CPME) as an environmentally benign solvent, resulting into a sustainable, safe and potentially automatable method for the synthesis of interesting strained compounds.
Keywords: aziridines; 2H-azirines; flow chemistry; green chemistry; organolithium compounds

(untitled) - Chen, T.-L.; Kim, H.; Pan, S.-Y.; Tseng, P.-C.; Lin, Y.-P.; Chiang, P.-C. (Sci. Total Environ., 2020)

(untitled) - Ratti, R. (SN Appl. Sci., 2020)

(untitled) - Loste, N.; Roldán, E.; Giner, B. (Environ. Sci. Pollut. Res., 2020)

(untitled) - Sharma, S.; Das, J.; Braje, W. M.; Dash, A. K.; Handa, S. (ChemSusChem, 2020)

Applications of Nanotechnology for Green Synthesis - Osei Akoto, C. (Industrial Applications of Green Solvents in Organic and Drug Synthesis for Sustainable Development of Chemical Process and Technologies, 2020)

(untitled) - Häckl, K.; Kunz, W. (C. R. Chim., 2018)

(untitled) - Fanelli, F.; Parisi, G.; Degennaro, L.; Luisi, R. (Beilstein J. Org. Chem., 2017)

(untitled) - Porta, R.; Benaglia, M.; Puglisi, A. (Org. Process Res. Dev., 2016)

(untitled) - Degennaro, L.; Carlucci, C.; De Angelis, S.; Luisi, R. (J. Flow Chem., 2016)

(untitled) - Plutschack, M. B.; Pieber, B.; Gilmore, K.; Seeberger, P. H. (Chem. Rev., 2017)

(untitled) - Bogdan, A. R.; Dombrowski, A. W. (J. Med. Chem., 2019)

Natural Products - Dembitsky, V. M.; Terent’ev, A. O.; Levitsky, D. O. (Aziridine Alkaloids: Origin, Chemistry and Activity, 2013)

(untitled) - Jat, J. L.; Paudyal, M. P.; Gao, H.; Xu, Q.-L.; Yousufuddin, M.; Devarajan, D.; Ess, D. H.; Kürti, L.; Falck, J. R. (Science, 2014)

(untitled) - Oseka, M.; Laudadio, G.; van Leest, N. P.; Dyga, M.; de Andrade Bartolomeu, A.; Goossen, L.; de Bruin, B.; Thiago de Oliveira, K.; Noel, T. (ChemRxiv, 2020)

(untitled) - Ielo, L.; Touqeer, S.; Roller, A.; Langer, T.; Holzer, W.; Pace, V. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ielo, L.; Pace, V.; Pillari, V.; Miele, M.; Castiglione, D. (Synlett, 2021)

(untitled) - Monticelli, S.; Colella, M.; Pillari, V.; Tota, A.; Langer, T.; Holzer, W.; Degennaro, L.; Luisi, R.; Pace, V. (Org. Lett., 2019)

(untitled) - Degennaro, L.; Trinchera, P.; Luisi, R. (Chem. Rev., 2014)

(untitled) - de Ceglie, M. C.; Musio, B.; Affortunato, F.; Moliterni, A.; Altomare, A.; Florio, S.; Luisi, R. (Chem. – Eur. J., 2011)

(untitled) - Dammacco, M.; Degennaro, L.; Florio, S.; Luisi, R.; Musio, B.; Altomare, A. (J. Org. Chem., 2009)

Heterocyclic Targets in Advanced Organic Synthesis - Alves, M. J.; Teixeira Costa, F. (2H-Azirines as electrophiles, 2010)

(untitled) - Davis, F. A.; Liang, C.-H.; Liu, H. (J. Org. Chem., 1997)

(untitled) - Carlson, R. M.; Lee, S. Y. (Tetrahedron Lett., 1969)

(untitled) - Ramkumar, N.; Voskressensky, L. G.; Sharma, U. K.; Van der Eycken, E. V. (Chem. Heterocycl. Compd., 2019)

(untitled) - Tiwari, D. K.; Maurya, R. A.; Nanubolu, J. B. (Chem. – Eur. J., 2016)

(untitled) - O'Brien, A. G.; Lévesque, F.; Seeberger, P. H. (Chem. Commun., 2011)

(untitled) - Cludius-Brandt, S.; Kupracz, L.; Kirschning, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Rossa, T. A.; Suveges, N. S.; Sá, M. M.; Cantillo, D.; Kappe, C. O. (Beilstein J. Org. Chem., 2018)

(untitled) - Koo, H.; Kim, H. Y.; Oh, K. (Org. Lett., 2019)

(untitled) - Chandrasekhar, D.; Borra, S.; Nanubolu, J. B.; Maurya, R. A. (Org. Lett., 2016)

(untitled) - Azzena, U.; Carraro, M.; Pisano, L.; Monticelli, S.; Bartolotta, R.; Pace, V. (ChemSusChem, 2019)

(untitled) - Perna, F. M.; Vitale, P.; Capriati, V. (Curr. Opin. Green Sustainable Chem., 2020)

(untitled) - Watanabe, K.; Yamagiwa, N.; Torisawa, Y. (Org. Process Res. Dev., 2007)

(untitled) - Zenzola, M.; Degennaro, L.; Trinchera, P.; Carroccia, L.; Giovine, A.; Romanazzi, G.; Mastrorilli, P.; Rizzi, R.; Pisano, L.; Luisi, R. (Chem. – Eur. J., 2014)

(untitled) - Parisi, G.; Capitanelli, E.; Pierro, A.; Romanazzi, G.; Clarkson, G. J.; Degennaro, L.; Luisi, R. (Chem. Commun., 2015)